Decentralized taxation and the size of government: evidence from Swiss State and local governments - Feld, Lars P.; Kirchgässner, Gebhard; Schaltegger, Christoph A. (Southern economic journal, 2010)
According to the Leviathan Model, fiscal federalism is a binding constraint on revenue-maximizing government. The competitive pressure of fiscal federalism reduces public sector size, as compared to unitary states. This study uses panel data of Swiss cantons from 1980 to 1998 to empirically analyze the effect of different instruments on government revenue and its structure. Because of the considerable tax autonomy of sub-national Swiss governments, it is possible to investigate different mechanisms by which fiscal federalism may influence government size. The results indicate that tax exporting has a revenue-expanding effect; whereas, tax competition favors a smaller size of government. Fragmentation has no robust effect on the size of government revenue for Swiss cantons. The overall effect of revenue decentralization leads to fewer tax revenues but higher user charges. Thus, revenue decentralization favors a smaller size of government revenue and shifts government revenue from taxes to user charges.